Cathelicidin-Derived Synthetic Peptide Improves Therapeutic Potential of Vancomycin Against Pseudomonas aeruginosa - Mohammed, Imran; Said, Dalia G.; Nubile, Mario; Mastropasqua, Leonardo; Dua, Harminder S. (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa (PA) is the leading cause of corneal blindness worldwide. A constant increase in multi-drug resistant PA strains have heightened the challenge of effectively managing corneal infections with conventional antibiotics. Antimicrobial peptides are promising antibiotic analogues with a unique mode of action. Cathelicidin-derived shorter peptides (FK13 and FK16) have previously been shown to kill a range of pathogens in both in vitro and in vivo systems. Here, our aim was to exploit the potential of FK13 or FK16 to enhance the anti-Pseudomonas activity of vancomycin, which normally has low clinical efficacy against PA. Our results have demonstrated that FK16 is more potent than FK13 against different PA strains including a clinical isolate from a patient’s ocular surface. FK16 was shown to enhance the membrane permeability of PAO1 at sub-inhibitory concentrations. Moreover, FK16 at lower concentrations was shown to increase the antibacterial susceptibility of vancomycin against PA strains up to 8-fold. The bactericidal synergism between FK16 and vancomycin was shown to be stable in the presence of physiological tear salt concentration and did not cause toxic effects on the human corneal epithelial cells and human red blood cells. Our results have revealed that sub-inhibitory concentration of FK16 could augment the antimicrobial effects of vancomycin against PA. It is anticipated that the future exploitation of the peptide design approach may enhance the effectiveness of FK16 and its application as an adjuvant to antibiotic therapy for the treatment of multi-drug resistant infections.